A Life Committed - Sbonelo Radebe (African Journal of Political Science)
Memoirs are usually one of the best avenues to understand people’s lives. They provide a first-hand account of one’s life from different perspectives. One of the problems with them is that they are expectedly full of biases. It is difficult for a memoirist to criticize herself and reveal everything. Perhaps at first glance, this is what one might expect from a memoir of a person like Essop Pahad (1939-2023). However, it is a marvelous work that offers a reader with great historical accounts of events and life well lived. Pahad served as the Minister in the Presidency from 1999 until 2008 under former President Thabo Mbeki who wrote a foreword to this book, “I am happy to commend this educative tour through many decades of exciting struggles for our liberation and a better world, as contained in this autobiography” (p17). To have served Thabo Mbeki for such a long time and remained his close ally for years is a significant sign that Pahad was a distinguished politician and intellectual in his own right.